Impacts of gender and location on the psychological wellbeing of Agricultural Science and Education Academic Staff - Kedinga, Marvin Ebot; Ugwuanyi, Christian Sunday (Universitas Negeri Padang, 2022)
There is a paucity of literature on the impacts of gender and location on the psychological well-being of agricultural science academic staff. This condition necessitated the use of an ex-post facto study with a sample of 46 University of Nigerian Agricultural Science and Education Academic Staff. The psychological wellbeing scale (α = .84) was used to collect data, which was based on the scientific research paradigm and quantitative research approach. The mean and t-test statistics were used to analyze the data. It was revealed that while gender had no significant impact on the academic staff’s psychological wellbeing, location had a significant impact on the academic staff’s psychological wellbeing. As a result, it was recommended that the university authority should make necessary accommodations to create a working environment that promotes the psychological wellbeing of academic staff irrespective of their location.